2006
DOI: 10.1177/153537020623100910
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein as a Prognostic Biomarker in Breast Cancer

Abstract: Breast cancer is the most common cancer in women, with a general upward trend in incidence. Basic and clinical breast cancer research has continued at a rapid pace, in the endeavor to understand the biology of the disease so as to improve management of patients. Besides traditional pathological indicators, expression of molecular markers in breast cancer has also been comprehensively investigated. This paper will focus on the prognostic utility of metallothioneins (MTs), a family of low molecular weight metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 59 publications
4
36
1
Order By: Relevance
“…A similar pattern of MT expression was observed in the examined benign lesions of mammary gland, including adenomas, adenofibromas and papillomas [37]. In lobular breast cancers as well as in other, less frequent histological types of the tumour, including mucinous carcinoma and papillary carcinoma, in most cases no MT expression or weak cytoplasmic reactions was shown [13,15]. On the other hand, a definitely increased MT expression was noted in ductal breast cancer, both in in situ and invasive forms.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…A similar pattern of MT expression was observed in the examined benign lesions of mammary gland, including adenomas, adenofibromas and papillomas [37]. In lobular breast cancers as well as in other, less frequent histological types of the tumour, including mucinous carcinoma and papillary carcinoma, in most cases no MT expression or weak cytoplasmic reactions was shown [13,15]. On the other hand, a definitely increased MT expression was noted in ductal breast cancer, both in in situ and invasive forms.…”
Section: Discussionsupporting
confidence: 74%
“…It is suggested that the role of MT in carcinogenesis and tumour progression could be linked to the involvement of MT in processes of cell proliferation and differentiation [10,12,13]. Using flow cytometry, the highest concentration of MT was found in cells at the end of G1 phase and at the threshold of G1/S phases [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, leptin stimulated a 40-fold induction in metallothionein 3 (MT3) gene expression. Metallothioneins are low-molecular-weight metal-binding proteins associated with proliferation, are overexpressed during breast cancer, and serve as potential biomarkers for poor cancer prognosis (Sens et al 2001, Bay et al 2006.…”
Section: Leptin Regulates Expression Of Cell Cycle and Apoptosis Genesmentioning
confidence: 99%
“…It is therefore not surprising that aberrant expression patterns of MTs can correlate with a number of pathologic conditions, including malignant progression. For example, high levels of MT-I and MT-IIA have been detected in many (but not all) human tumors, including those of the breast, prostate, cervix, testes, kidney, bladder, brain, and oral epithelium (19)(20)(21)(22)(23)(24)(25). Underlying molecular mechanisms are believed to include the ability of MT to activate survival pathways and confer resistance against drug and radiation therapy (5,(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%